The transnational earth: Evolution meets the World Heritage in model development scenarios for a globally inclusive knowledge economy - Hana Ayala (Frontiers in Environmental Economics)
The article explores the global promise of the natural reserves of the knowledge capital that permeate the earth's evolutionary and ecological connectivity and may constitute the greatest reserve of the sustainability and common good of the global knowledge economy. It builds the case for valuing knowledge yielded by basic research that inter-relates natural properties and processes across and beyond national jurisdictions as a mapping tool for World Heritage nominations as well as for collaborations that would deliver a unique stimulus for building conservation-premised transnational knowledge economies that fully engage the developing world. This perspective is vetted in the South Pacific Island Region, the Eastern Tropical Pacific, and the Isthmus of Panama, via model approaches crafted to empower the World Heritage instrument to vitalize the economic might of scientific exploration of the planet's biodiversity and to play a central role in unlocking the potential of nature's knowledge-rich evolutionary pathways to redefine the world's economic geography. The roadmap toward unleashing the economic energy of transnational research endeavors as stewards of new conservation frontiers is offered with a business model grounded in the confluence of knowledge and wonder and contributing an investment platform that encourages a globally shared benefit of the knowledge economy.